Waiting for Godot - Beckett, Samuel (Films for the Humanities & Sciences, 1987)
Gedalof and Professor Gerald Parker literally take to the stage to explore the many opportunities at work in this enigmatic Beckett drama. They alternate between performing various scenes of the play and analyzing them.